Capital Structure and Firm Value: Evidence from China's Internet Industry - WANG, QIN (2020)
This study examines the relationship between capital structure and firm value as well as the determinants of capital structure from an industry perspective, by using the sample data of listed companies classified in China’s internet industry sector on the Shanghai Exchange and Shenzhen Exchange with the time of 2010 to 2019 and applying the Fixed Effects estimator to run the panel data regressions. The results of this study found that for companies belong to China’s internet industry, when using total debt ratio as a measure of capital structure and firms’ market value as an indicator of firm value, the relationship between capital structure and firm value is significantly negative. For the determinants of capital structure, the regression results illustrate that firm value, firm performance, tangibility assets structure, firm size, and firm age are influencers of capital structure and are negatively related with it. On the contrary, capital structure is positively related to explanators of firms’ assets growth rate, state ownership, special treatment risk warning signal, and treating online games as main business types. When using short-term debt ratio as a measure of capital structure, the results are similar. However, the relationship between capital structure and firm size becomes positive when using long-term debt ratio as a measure of capital structure.